Penyalahgunaan Pemanfaatan Ruang Rusunami di Kalibata City Berdasarkan Undang-Undang Nomor 6 Tahun 2023 - Sugiarto, Fiona (JURNAL MINUTA, 2025)
The dynamic development of society has increased the need for houses. In fact, space is increasingly limited and the population is increasing. So, it is necessary for space to be utilised as in Article 33 of the 1945 Constitution relating to space utilization. The utilization of space in question is the provision of an area that is used as a place of residence for the community in order to achieve a welfare state. In this case, simple flats are owned as one of the implementations of space utilization by the government because it is aware of the arrangement, management, and utilization of space. Owned simple flats are included in the category of public flats intended for low-income people. In relation to space utilization, flats are used as residential places but in fact, they are used as places of prostitution that occurred in Kalibata City in 2020, involving minors who were forced to serve four men. This is not in accordance with the utilization of flats that can be reviewed from KKPR and Law Number 6 Year 2023 in relation to norms, standards, procedures, and criteria. This research is a legal research with a statutory and conceptual approach. The primary source of legal material in this research comes from laws and regulations, while secondary legal material is legal literature. This research aims to describe the correlation of spatial planning with flats and government supervision related to the misuse of simple flats owned in Kalibata City.